ETHNOPHARMACOLOGICAL STUDY OF PLANTS IN BAHALAYUNG VILLAGE AMONG THE DAYAK BAKUMPAI COMMUNITY IN BARITO KUALA REGENCY - Fiqriani, Rizka Annida; Biyatmoko, Danang; Badruzsaufari, Badruzsaufari (Universitas PGRI Sumatera Barat, 2024)
The ethnopharmacological study aims to document and analyze the use of medicinal plants by the Dayak Bakumpai community in Bahalayung Village, Barito Kuala Regency. This research employs a qualitative descriptive approach, utilizing in-depth interviews, participatory observation, and documentation methods. Key informants include community leaders, traditional healers, and local users of medicinal plants. The findings reveal that the Dayak Bakumpai community utilizes a variety of local plants to treat ailments such as fever, wounds, digestive disorders, and skin diseases. A total of 15 medicinal plant species were identified as commonly used; however, knowledge about their medicinal applications remains limited. This knowledge is traditionally passed down orally across generations and is deeply rooted in the community's cultural practices. The presence of active compounds such as flavonoids, alkaloids, and tannins in several plants indicates significant pharmacological potential. This study underscores the importance of preserving traditional knowledge as a means of safeguarding biodiversity and cultural heritage. Additionally, further research is needed to scientifically validate the safety and efficacy of these medicinal plants, supporting the development of evidence-based traditional medicine.